2016
DOI: 10.4314/bajopas.v9i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial studies on the ethyl acetate fraction of the stem bark extract of <i>Uapaca togoensis</i> Pax. (Euphorbiaceae) in mice

Abstract: Uapacatogoensis of family Euphorbiaceae ailments including pneumonia, cough, fever, rheumatism, vomitting and epilepsy fraction of the stem bark was extract was studied Lorke's method studied in chloroquine-sensitive in each group were used. Group 1 and 4 were administered with 250, 500, and 1000 mg respectively, while group 5 was administered with 5mg chloroquine/kg body weight. The doses were all administered orally. All doses of the extract produced significant, dose dependent, chemo suppressive activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is noteworthy that the chemosuppression produced by the n-butanol fraction of the plant was better than that of the ethyl acetate fraction reported in a previous study. 21 This difference in antimalarial activity may be linked to the fact that the ethyl acetate fraction was devoid of saponins and tannins and studies have reported these phytochemicals to possess antimalarial activity. 42 Research on medicinal plants contributed to the isolation of compounds with potent antimalarial activity including artemisinin and quinine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the chemosuppression produced by the n-butanol fraction of the plant was better than that of the ethyl acetate fraction reported in a previous study. 21 This difference in antimalarial activity may be linked to the fact that the ethyl acetate fraction was devoid of saponins and tannins and studies have reported these phytochemicals to possess antimalarial activity. 42 Research on medicinal plants contributed to the isolation of compounds with potent antimalarial activity including artemisinin and quinine.…”
Section: Resultsmentioning
confidence: 99%
“…18 The ethyl acetate fraction of the stem bark also exhibited antiplasmodial, analgesic and anti-inflammatory properties. [21][22][23] The present study aimed to evaluate the antimalarial activity of the n-butanol fraction of Uapaca togoensis with the aim of providing data from which possible compounds responsible for the observed pharmacological activity can be isolated.…”
mentioning
confidence: 99%
“…Various parts of the plant have been used in folk medicine for wide variety of remedies such as fever, rheumatism, vomiting, fatigue and epilepsy [14]. Previous pharmacological studies revealed that extracts of Uapaca togoensis possesses antifungal, antimocrobial, antiplasmodial, analgesic, anti-inflammatory, cytotoxic and antimicrobial properties [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is used in traditional medicine to treat pneumonia, cough, fatigue, fever, rheumatic pain, vomiting, and epilepsy [9,10]. Screening studies on the organs of this plant have confirmed its antibacterial [10], larvicidal [11], antifungal and antimicrobial [12,13], antiplasmodial [12], and cytotoxic [14] virtues. It is a species highly appreciated by nearly 80% of the population of the central region of Togo as an excellent firewood with easy combustion [15].…”
Section: Introductionmentioning
confidence: 99%